Evaluasi Uji Diagnostik POSSUM Dan P-POSSUM Sebagai Prediktor Mortalitas Pada Pasien Laparotomi Emergensi Di Rumah Sakit Umum Daerah Dr. Zainoel Abidin Banda Aceh - Novrianda Eka Putra; Muslim Muslim; Jufriady Ismy; Ferry Erdani; Imam Hidayat (Majalah Kedokteran Indonesia, 2025)
Introduction: Laparotomy is a frequent surgical procedure carried out in emergency settings due to various indications and related to a considerable amount of postoperative mortality rate. POSSUM and P-POSSUM are known as two of the most favorable methods to calculate the likelihood of postoperative mortality, so that optimization of patient management can be achieved. The purpose of this research is to assess the predictive power of POSSUM and P-POSSUM scoring systems for emergency laparotomy patients in terms of accuracy, sensitivity, specificity, and Area Under the Curve (AUC) value. Method: This study uses an observational analytical method with a prospective cohort approach, and was performed at Dr. Zainoel Abidin Regional General Hospital Banda Aceh since January until May 2024. Mortality status was observed for 30 days after surgery. The accuracy of POSSUM and P-POSSUM was assessed based on sensitivity, specificity, and AUC values obtained from the Receiver Operating Characteristic (ROC) curve. Results: A total of 13 subjects experienced mortality within 30 days after surgery out of 29 subjects involved in this study. Analysis based on the ROC curve shows that POSSUM and P-POSSUM equally have 100% sensitivity and 75% specificity. The AUC values obtained were 0.851 and 0.837 respectively. Conclusion: POSSUM and P-POSSUM scoring systems have good accuracy as mortality predictors in emergency laparotomy patients.